2012
DOI: 10.1175/2011jhm1372.1
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel Analysis of Energy and Water Fluxes: Intercomparisons between Operational Analyses, a Land Surface Model, and Remote Sensing

Abstract: Using data from seven global model operational analyses (OA), one land surface model, and various remote sensing retrievals, the energy and water fluxes over global land areas are intercompared for 2003/04. Remote sensing estimates of evapotranspiration (ET) are obtained from three process-based models that use input forcings from multisensor satellites. An ensemble mean (linear average) of the seven operational (mean-OA) models is used primarily to intercompare the fluxes with comparisons performed at both gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 73 publications
2
25
0
Order By: Relevance
“…These data have provided a wealth of spatially and temporally varying information across a range of Earth system processes, including soil moisture (Liu et al, 2011a), vegetation change (Tucker et al, 2005;Liu et al, 2011bLiu et al, , 2013, groundwater (Famiglietti et al, 2011;Richey et al, 2015) and precipitation (Huffman et al, 1995;Nesbitt et al, 2004), enabling a capacity to enhance our understanding and description of regional-and global-scale water cycles and their spatial and temporal variability. While evaporation represents the key process returning the Earth's surface water to the overlying atmosphere and provides the linking mechanism between the water and energy cycles, it is only in relatively recent times that effort has been directed towards the development of global products (Mu et al, 2007;Fisher et al, 2008;Vinukollu et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data have provided a wealth of spatially and temporally varying information across a range of Earth system processes, including soil moisture (Liu et al, 2011a), vegetation change (Tucker et al, 2005;Liu et al, 2011bLiu et al, , 2013, groundwater (Famiglietti et al, 2011;Richey et al, 2015) and precipitation (Huffman et al, 1995;Nesbitt et al, 2004), enabling a capacity to enhance our understanding and description of regional-and global-scale water cycles and their spatial and temporal variability. While evaporation represents the key process returning the Earth's surface water to the overlying atmosphere and provides the linking mechanism between the water and energy cycles, it is only in relatively recent times that effort has been directed towards the development of global products (Mu et al, 2007;Fisher et al, 2008;Vinukollu et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties emerging from such aggregations can often reduce the confidence in any subsequent model performance ranking. One initial effort addressing this was the study of Vinukollu et al (2011a), which used the Surface Energy Balance System (SEBS) model (SEBS; Su, 2002), a twosource Penman-Monteith scheme by Mu et al (2007) and a three-source model based on parameterising the PriestleyTaylor model (PT-JPL) (Fisher et al, 2008) to estimate global evaporation for the period 2003-2004. The Vinukollu et al (2011a analysis revealed that the modelled instantaneous evaporation (coinciding with the time of satellite overpass) was in reasonable agreement with locally observed evaporation at 12 eddy-covariance towers across the United States, with correlations ranging from 0.43 to 0.54.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been used to estimate actual evapotranspiration at local (Ershadi et al, 2014) and global scales in various studies (e.g. Badgley et al, 2015;Ershadi et al, 2014;Vinukollu et al, 2011), including the recent LandFlux and WACMOS-ET efforts. Detailed descriptions of the model are provided in those references.…”
Section: Pt-jplmentioning
confidence: 99%
“…Recent studies that also make use of thermal and optical sensors range from "classical" rainfall-runoff modelling with remotely sensed pattern comparison (like our contribution) to integrated data assimilation systems. Examples of the former are from Boegh et al (2004) for 10 km 2 of agricultural landscape in Denmark and Vinukollu et al (2012) with a global ET pattern comparison; as well as a substantial contribution from Schuurmans et al (2011) who first compare and then assimilate the modelled and remotely sensed actual ET patterns of an area of 70 km 2 in the middle of the Netherlands; however, observed differences between the two data sources remain partly unexplained.…”
Section: Hydrological Modelling and Remote Sensingmentioning
confidence: 99%